The Influence of Brand Trust, Brand Image and Perceived Quality on Pepsodent Toothpaste Brand Loyalty (Study on the Community of Tuah Madani District, Pekanbaru City) - Rachmad, Ferizal; Mardatilla, Mardatilla (Basecamp Economics PubMed, 2024)
The purpose of this study was to determine whether the influence of Brand Trust, Brand Image and Perception of Quality on Brand Loyalty in the community of tuah madani sub-district, pekanbaru city. The rapid development of the company has led to intense competition between companies to win the hearts of consumers. This is indicated by the increasing number of companies that produce similar products, in order to meet consumer needs. The data collection technique used a questionnaire. The population in this study were pepsodent toothpaste users in the tuah madani sub-district of pekanbaru city 2024. In this study, the sample amounted to 100 respondents using purposive sampling technique. Data analysis used in this study is quantitative with multiple linear regression methods. Based on the results of the simultaneous test, it can be seen that the variables of brand trust, brand image and perceived quality together have an effect on the loyalty of the pepsodent toothpaste brand in the community of tuah madani subdistrict, pekanbaru city. Then test partially, from this test it can be seen that the brand trust variable has a significant effect on brand loyalty and the brand image variable has a significant effect on brand loyalty and perceived quality has a significant effect on brand loyalty. Obtained R square value of 0.737 or equal to 73.7% while the remaining 26.3% is influenced by other variables not included in this study.